European Cosmopolitan Solidarity - Stevenson, Nick (Sage, 2006)
The idea of a cosmopolitan Europe continues to be central to contemporary debates within post-national citizenship. However, much of the writing in this area remains disconnected from the need to reinvent European social democracy that questions the centrality of work and racist nationalism. This article argues that a revived European Left would need to move beyond specifically liberal concerns with procedure to articulate a view of European futures that both deconstructed neo-liberalism and embraced more convivial collective futures. This would entail the combination of a post-material politics that sought to critique the centrality of employment while granting citizens a basic income or forms of civic labour and a more concerted attempt to break with a racialized politics based upon the fear of the ‘Other’. In conclusion, it is argued that the urgent political task of the future is to reinvent a sense of Europeaness that has both a substantive content, but that does not become mobilized by an exclusive cultural politics.